2018
DOI: 10.20307/nps.2018.24.1.40
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and Anti-inflammatory Activity of Six Halophytes in Korea

Abstract: − The aim of this study was to measure and compare polyphenol content, antioxidant, and antiinflammatory activity of six halophytes (Limonium tetragonum, Suaeda glauca, Suaeda japonica, Salicornia europaea, Triglochin maritimum, and Sonchus brachyotus). Depending on the total polyphenol content, the plants were categorized into two groups: (1) a high total polyphenol content group that included L. tetragonum, S. brachyotus, and S. europaea, and, (2) a low total polyphenol content group consisting of S. glauca,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 24 publications
1
15
0
Order By: Relevance
“…For instance, the presence of immunomodulatory compounds in crude extracts was demonstrated via RAW 264.7 macrophage cell line assays [ 8 ]. Moreover, the antioxidant activity of S. europaea was measured via the 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging, hydroxyl radical scavenging, and reactive oxygen species (ROS) generation assays [ 9 ]. The antihyperglycemic and antihyperlipidemic activities of this plant were also demonstrated in mice fed with a high-fat diet [ 10 ] and another study reported that a polysaccharide extract from this plant exhibited anti-inflammatory activity in vitro and in vivo [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the presence of immunomodulatory compounds in crude extracts was demonstrated via RAW 264.7 macrophage cell line assays [ 8 ]. Moreover, the antioxidant activity of S. europaea was measured via the 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging, hydroxyl radical scavenging, and reactive oxygen species (ROS) generation assays [ 9 ]. The antihyperglycemic and antihyperlipidemic activities of this plant were also demonstrated in mice fed with a high-fat diet [ 10 ] and another study reported that a polysaccharide extract from this plant exhibited anti-inflammatory activity in vitro and in vivo [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Halophyte is a plant with unique adaptive mechanisms that naturally survives in saline environments such as tidal flats, sand dunes, and coasts (Lee et al 2018a(Lee et al , 2018b. Regarding the successful tolerance in hostile conditions, for example, salinity, UV radiation, and extreme temperature, HP is believed to allow valuable secondary metabolites including polyphenol, carotenoid, and vitamins to cope with those stress-overwhelmed environments (Jdey et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…; Lee et al 2018aLee et al , 2018b. However, the inhibitory effect screening of the Jeju plant by Moon et al (2010) unlikely found a slight inhibition of elastase, while no inhibitory effect of tyrosinase was detected at the concentration of 500 μg/ml.…”
mentioning
confidence: 97%
“…brachyotus is a perennial plant belonging to Asteraceae family and its young leaves have been used for medicinal resources in Korea (Nugroho et al, 2012). S. brachyotus has been shown to exhibit various biological activities, such as antioxidant, anti-inflammatory, antibacterial and antidiabetic activities (Lee et al, 2018;Li et al, 2017;Xia et al, 2011); however, very limited knowledge is available regarding the isolation and identification of its secondary metabolites. Therefore, in the current study, we isolated secondary metabolites from S. brachyotus and evaluated their antioxidant and anti-inflammatory activities.…”
Section: Discussionmentioning
confidence: 99%
“…The young leaves of S. brachyotus, which are known to possess diuretic activity, are also used to treat hepatitis and hemorrhage in Korea (Nugroho et al, 2012). S. brachyotus has been reported for exhibiting biological activities, including antioxidant, anti-inflammatory, antibacterial and antidiabetic activities (Lee et al, 2018;Li et al, 2017;Xia et al, 2011). But, many studies have described the isolation and identification of secondary metabolites from Sonchus species, however, investigations of S. brachyotus have been scarce.…”
Section: Introductionmentioning
confidence: 99%